Integration of small RNAs from plasma and cerebrospinal fluid for classification of multiple sclerosis - Needhamsen, Maria; Khoonsari, Payam Emami; Zheleznyakova, Galina Yurevna; Piket, Eliane; Hagemann-Jensen, Michael; Han, Yanan; Gierlich, Jannik; Ekman, Diana; Jagodic, Maja (Frontiers in Genetics, 2022)
Multiple Sclerosis (MS) is an autoimmune, neurological disease, commonly presenting with a relapsing-remitting (RRMS) form, that later converts to a secondary progressive (SPMS) stage. Early treatment slows disease progression, hence, accurate and early diagnosis is crucial. Recent advances in large-scale data processing and analysis have progressed molecular biomarker development. Here, we focus on small RNA data derived from cell-free cerebrospinal fluid (CSF), CSF cells, plasma and peripheral blood mononuclear cells (PBMCs), as well as CSF cell methylome data, from people with RRMS (n = 20), clinically/radiologically isolated syndrome (CIS/RIS, n = 2) and neurological disease controls (n = 14). We applied multiple co-inertia analysis (MCIA), an unsupervised and thereby unbiased, multivariate method for simultaneous data integration and found that the top latent variable classifies RRMS status with an Area Under the Receiver Operating Characteristics (AUROC) score of 0.82. Variable selection based on Lasso regression reduced features to 44, derived from the small RNAs from plasma (20), CSF cells (8) and cell-free CSF (16), with a marginal reduction in AUROC to 0.79. Samples from SPMS patients (n = 6) were subsequently projected on the latent space and differed significantly from RRMS and controls. On contrary, we found no differences between relapse and remission or between inflammatory and non-inflammatory disease controls, suggesting that the latent variable is not prone to inflammatory signals alone, but could be MS-specific. Hence, we here showcase that integration of small RNAs from plasma and CSF can be utilized to distinguish RRMS from SPMS and neurological disease controls.